IMPLEMENTATION OF PROVISIONS ARTICLE 7 PARAGRAPH 2 OF LAW NUMBER 11 OF 2012 CONCERNING CHILDREN CRIMINAL JUSTICE - Fransiska Novita Eleanora; Sri Wahyuni (JURNAL ILMIAH LIVING LAW, 2020)
Children as successors to the ideals of the struggle of the nation must always be protected by the existence of their rights, including children who have legal obligations, meaning that the child if possible is not sentenced but is resolved by way of deliberation for consensus and a familial nature commonly referred to as diversion. . Settling this diversion so that children can be held responsible, remove the stamp or stigma attached to the child, and there is no sense of revenge between the perpetrator and the victim. But the obstacle in diversion is a crime committed by a child no more than 7 (seven) years and is not a repetition or recidivist, so the provisions of article 7 paragraph 2 are considered not to provide justice to children who have problems with the law, because the diversion must also ask the victim's agreement. , exceptions to the nature of minor criminal offenses, no victims, and losses suffered not exceeding the local minimum wage. The research method is normative juridical by reviewing literature and legislation relating to the problem under study, and the result is diversion prioritizing the best interests of children as perpetrators and victims in accordance with restorative justice and prioritizing children's rights to get justice in accordance with the protection of rights of childKeywords: children, law, criminal, justice